Impact of multifaceted interventions on the knowledge, attitude, and practice of adverse drug reactions reporting among healthcare workers in Vietnam: a comparative intervention study - Pham, Hong Tham; Tran Doan, Minh-Thy; Dang Thi, Thuy; Nguyen Tuan, Dung; Tran, Minh-Hoang; Nguyen, Thao Ngoc Phuong (Frontiers in Pharmacology, 2024)
Knowledge, attitude, and practice of Adverse Drug Reactions (ADRs) and ADRs reporting among healthcare workers were related to the quality and ADRs reporting rate. The aim of this study was to evaluate the effectiveness of the multifaceted interventions on knowledge, attitude, and practice (KAP) of healthcare workers and to compare the proportion of spontaneous ADRs reports at the study center, before and after instituting multifaceted interventions.A comparative intervention study was conducted among healthcare workers at the hospital. The participants were asked to complete a questionnaire before and after instituting the multifaceted interventions to assess the KAP of ADRs and their reporting. The impact of the multifaceted interventions was assessed by comparing their correct responses to the KAP questions and the proportion of spontaneous ADRs reports before and after the interventions. The pre-and postintervention scores for KAP questions were compared usingMcNemar test by R Language. 388 healthcare workers completed the study. The proportion of participants qualified for ADRs reporting increased significantly, from 73.5% (pre -intervention) to 99.2% (postintervention) for knowledge scores, from 70.6% to 91.8% for attitude scores, and from 81.4% to 97.2% for practice scores (p < 0.001). Similarly, the number of spontaneous ADRs reports increased by 31% after 3 months of interventions.Multifaceted interventions instituted at the study center improved the knowledge, attitude, and practice of health workers towards ADRs and spontaneous reporting. It would be beneficial to implement such interventions in other hospitals in Vietnam.